Human Amniotic Membrane Graft in the Management of Peripheral Hypertrophic Subepithelial Corneal Degeneration: A Case Report - Pietro Rosetta; Bruno Battaglia; Sakshi Watarkar; Alessandro Feo (Case Reports in Ophthalmology)
Introduction: In this report, we describe the case of peripheral hypertrophic subepithelial corneal degeneration (PHSCD), managed with surgical excision and a human amniotic membrane (hAM) graft. Case Presentation: A 45-year-old female Caucasian patient presented with decreased vision, itching, and burning in both eyes, and a presence of pseudopterygium in the right eye, causing visual decline. Routine ocular exams and anterior segment OCT led to the diagnosis of PHSCD, after a careful differential diagnosis with other similar clinical occurrences. Subsequently, the patient was successfully managed with surgical intervention and an amniotic membrane graft placement. Conclusion: PHSCD is a rare disease, which in advanced cases can be successfully managed with hAM graft. No recurrence of the lesions was observed at 1-year follow-up in our patient.